2018
DOI: 10.1039/c8sc02400f
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen atom transfer reactivity of sulfinic acids

Abstract: Sulfinic acids are characterized to be very good H-atom donors to each of alkyl and alkoxyl radicals. In order to participate in useful radical chain reactions, the sulfonyl radicals must undergo fast propagating reactions to avoid autoxidation, which is surprisingly rate-limited by the reaction of sulfonyl radicals with oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…undergoes hydrogen abstraction from 1 to regenerate I (step d ). Step d is likely to be thermodynamically unfavorable, [7] and thus an excess amount of 1 is required to step forward [12] …”
Section: Methodsmentioning
confidence: 99%
“…undergoes hydrogen abstraction from 1 to regenerate I (step d ). Step d is likely to be thermodynamically unfavorable, [7] and thus an excess amount of 1 is required to step forward [12] …”
Section: Methodsmentioning
confidence: 99%
“…Finally, elimination a sulfinyl radical generates the key double bond, providing the prenylated aryl or alkyl product. The sulfinyl radical abstracts a hydrogen atom from an H‐atom donor to generate sulfinic acid, the presence of which has been confirmed by doping experiments (see SI). During the prenylation reaction, we observed that some of 1k underwent a formal 1,3‐rearrangement to form the thermodynamically more stable, linear, and non‐productive prenylated sulfone.…”
Section: Resultsmentioning
confidence: 75%
“…Sodium sulfinates can be replaced by sulfinic acids 47, which in a similar way, upon illumination, release the sulfonyl radical thus overcoming through photocatalysis the problems related to autoxidation which limited their application over the past years. 23 Both reagents are bench stable and non-odorous compounds which are easily preparable and commercially available. In 2015, almost contemporary to the group of König, a synthesis of sulfones was proposed by Wang coworkers starting from sulfinic acids.…”
Section: Scheme 16 Carboxylic Acids Decarboxylative Sulfonylation By Dual Photocatalysismentioning
confidence: 99%
“…Scheme 17 Application of the dual photocatalytic approach to carboxylic acids decarboxylative sulfonylation in the synthesis of bicalutamide Sodium sulfinates can be replaced by sulfinic acids 47, which in a similar way, upon illumination, release the sulfonyl radical thus overcoming through photocatalysis the problems related to autoxidation which have previously limited their application. 23 Both reagents are bench stable and non-odorous compounds and they are easily prepared or commercially available. In 2015, almost contemporary to König, 6 a synthesis of sulfones was proposed by Wang starting from sulfinic acids.…”
Section: Scheme 15 Proposed Mechanism For the Visible-light-induced Decarboxylative Sulfonylation Of Cinnamic Acidsmentioning
confidence: 99%
See 1 more Smart Citation